2021
DOI: 10.3390/pr9081431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar on Soil Aggregation and Distribution of Organic Carbon Fractions in Aggregates

Abstract: Soil aggregates are among crucial factors for determining both the quality and erosion resistance of soils. Biochar is a soil amendment that has seen increasing use to improve specific soil properties, mainly the physical structure and the preserving capacity of water and nutrients, as well as sequestration of soil organic carbon. In this study, we applied the rice husk biochar (RHB) and cattle manure compost (COM) in a sandy loam rural soil, which is widely distributed in southern Taiwan, to investigate the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…Our result showed that biochar-based compost changed the soil properties more efficiently than biochar-only treatment. Although there was no significant increase in soil properties after 1 year of the biochar-only treatment, we suggest that the soil porosity would be significantly higher after repeating or extending the biochar amendments due to the porous internal structure of biochar [20]. This indicates that the water holding capacity would increase.…”
Section: Soil Physicochemical Parameters Shaped Urban Tree-associated...mentioning
confidence: 67%
See 1 more Smart Citation
“…Our result showed that biochar-based compost changed the soil properties more efficiently than biochar-only treatment. Although there was no significant increase in soil properties after 1 year of the biochar-only treatment, we suggest that the soil porosity would be significantly higher after repeating or extending the biochar amendments due to the porous internal structure of biochar [20]. This indicates that the water holding capacity would increase.…”
Section: Soil Physicochemical Parameters Shaped Urban Tree-associated...mentioning
confidence: 67%
“…Processes 2022, 10, 682 2 of 14 Biochar and organic compost amendment have been promoted to improve soil physical, chemical, and biological properties in agriculture for years [17][18][19][20]. Biochar as a carbon-rich material produced by pyrolysis can increase soil water-holding capacity [21] and nutrient availability in different types of soil [22,23], and pH in acidic soils [24].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, wastes of different origin (urban, industrial or agricultural) are frequently used as organic amendments in agricultural management practices, as their potential to improve soil physical structure, stimulate soil microbial activity, and maintain soil fertility and quality have been well documented (El-Naggar et al, 2019;Ibrahimi et al, 2022;Zhang et al, 2022). The suitable management of organic amendments is a good way to maintain appropriate soil aggregate stability and structure, as basic factors for enhancing soil physical fertility (Lee et al, 2021;Manfredi et al, 2019) avoiding soil erosion, preventing and reversing soil degradation through the addition of OM to soils (Medina et al, 2012;Unagwu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Soil structure is a crucial component of soil quality (Pagliai et al, 2004), and soil organic matter (SOM) plays a key role in the development of soil structure (Abiven et al, 2009; Boyle usually a slow process and can be hampered by regulations surrounding nitrogen management. Recently, there has been a growing interest in biochar for use as a soil amendment to enhance soil aggregation and structure (Juriga & Šimanský, 2018;Lee et al, 2021). Biochar is derived from the pyrolysis of renewable carbon sources such as crop residues and wood (Lehmann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%